PELATIHAN PEMBERDAYAAN JUS SIRSAK SEBAGAI MINUMAN KESEHATAN OLAHAN ALAMI PENCEGAH KANKER - Hartati, Lesi; Asmawati; Hendarmin, Rum; Syafitri, Lili (Transpublika Publisher, 2021)
Indonesia is a paradise for plants, with numerous advantages for human life. It is possible to process Indonesia's natural resources to support the family economy while also benefiting health and being useful in treating various diseases, and many of these resources contain the vitamins that the body's organs require to increase energy. The health advantages of soursop plants are substantial, and the fruit is tasty to consume as is. Sometimes it grows naturally in people's yards; at other times, it is planted intentionally by the community for economic purposes. Apart from the fruit, soursop leaves can also be used to treat cholestorel when combined with additional spices such as betel leaves and a pinch of salt. Making soursop juice is simple if the fruit is ripe, although soursop fruit that is not ripe yet can be fried and the taste is similar to sweet potatoes. The business potential related with soursop seed planting are considerable. Along with the fruit, the leaves are beneficial for health since they contain a variety of vitamins that the body need.